United Arab Emirates : 2011 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
The economic recovery in the U.A.E. is gaining strength, but subject to increased regional uncertainty. The government should undertake cost-benefit analysis and implement projects that have high economic return. In order to reduce government-related entities (GRE) risks, the authorities should complete restructuring of GRE debt and communicate their strategy by developing a GRE risk management framework. The central bank has taken steps in strengthening risk monitoring and the management system. The progress made by National Bureau of Statistics (NBS) in establishing macroeconomic statistics proved an important step toward developing statistical capacity.